Relationships between Sociosexuality and Dermatoglyphic Traits - Ingrová, Pavlína; Králík, Miroslav; Polcerová, Lenka; Pavlíková, Věra; Klíma, Ondřej; Čuta, Martin (Anthropological Review, 2025)
In humans, prenatal development of brain dispositions to sex differences in mating behavior is difficult to study directly. Indirect prenatal markers, including dermatoglyphics, present a viable option.In this study we tested a hypothesis that some radio-ulnar contrasts in dermatoglyphic ridge counts could be related with human sociosexuality.Sociosexual Orientation Inventory (SOI) data from 180 young adults, along with fingerprints of their terminal phalanges (via hand scanning) were collected, and relationships between SOI and dermatoglyphics were analyzed.Typical sex differences in SOI were recorded with higher scores in males and lower in females. Among other results we found that on the index finger lower number of triradii and cores (i.e., mostly in loop type dermatoglyphic patterns) and radial-biased within-finger asymmetry in ridge counts typical for ulnar loops were connected with typical sex differences in SOI (higher in males and lower in females) while in subjects possessing an opposite dermatoglyphic arrangement – higher numbers of cores and triradii and ulnar-biased within-finger ridge count asymmetry typical in radial loops – sex differences in SOI scores disappeared. Recognized significant and systematic trends were mostly connected with variables derived from dermatoglyphic features on the 2nd and 4th fingers.Possible relationships with prenatal androgen causation are discussed.